Political budget cycles or voters as fiscal conservatives? : evidence from Colombia (2005)
Theoretical models of the political budget cycle suggest that electoral manipulation of government expenditures can take the form of changes in the composition of spending, without impacting the overall budget or the deficit, and that the form and extent of this manipulation depend on the fiscal preferences of voters. In this paper, I use data on government expenditures and election outcomes in Colombia to provide an integrated analysis of voting behavior and the preelectoral dynamics of government spending. I emphasize potential changes in the composition, rather than the size, of the budget. I find that components of the budget that can be identified with targeted spending grow, and that non-targeted spending contracts, in the year preceding an election. Consistently, I find that voters reward the preelection increases in targeted spending, but punish incumbents who run high deficits before the election.